INVESTIGATING THE RELATIONSHIP AMONG INSTRUCTORS' TECHNOSTRESS AND TECHNOLOGY ACCEPTANCE LEVELS AND THEIR ATTITUDES TOWARDS DISTANCE EDUCATION - Uğraş, Hilal; Gömleksiz, Mehmet Nuri (My University, 2023)
In this study, the aim was to examine the relationship between instructors' technostress and technology acceptance levels and their attitudes towards distance education. The sample of this study consists of 957 instructors who use distance education method in their courses in universities located in the Eastern Anatolia Region of Turkey. Quantitative method was used in the study. The research collected data with the \"Attitude Toward Distance Education Scale\", \"Technostress Scale\" and \"Technology Acceptance Scale\". The data obtained were analyzed using SPSS 22 and Amos 26. The data were analyzed using t-test, ANOVA, Bonferroni, correlation, multiple regression and structural equation modeling. In addition, the eta-square (?2) value was calculated to determine the degree of significant difference between the groups. Research findings revealed that there were found to be significant differences in instructors' attitudes towards technostress, technology acceptance and distance education in terms of gender, discipline, title and seniority variables. In addition, technological acceptance predicts technostress directly and negatively; technological acceptance predicts attitude towards distance education directly and positively; technostress predicts attitude towards distance education directly and negatively.As a result, it has been determined that the technostress and technological acceptances of the instructors affect their attitudes towards distance education.
Keywords: Instructors; Technostress; attitude towards distance education; technological acceptance; higher education.